2005
DOI: 10.1146/annurev.micro.58.030603.123749
|View full text |Cite
|
Sign up to set email alerts
|

Signaling in the Arbuscular Mycorrhizal Symbiosis

Abstract: Many microorganisms form symbioses with plants that range, on a continuous scale, from parasitic to mutualistic. Among these, the most widespread mutualistic symbiosis is the arbuscular mycorrhiza, formed between arbuscular mycorrhizal (AM) fungi and vascular flowering plants. These associations occur in terrestrial ecosystems throughout the world and have a global impact on plant phosphorus nutrition. The arbuscular mycorrhiza is an endosymbiosis in which the fungus inhabits the root cortical cells and obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
449
0
26

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(494 citation statements)
references
References 188 publications
7
449
0
26
Order By: Relevance
“…The rhizosphere is a zone of intense signaling between microbes, including mycorrhizal fungi, and plant roots (Bais et al 2004;Harrison 2005;Bais et al 2006;Paszkowski 2006). For example, experiments conducted using both field soils and in vitro cultures show that compounds (e.g.…”
Section: Mechanism 3: Biochar Alters the Signaling Dynamics Between Pmentioning
confidence: 99%
“…The rhizosphere is a zone of intense signaling between microbes, including mycorrhizal fungi, and plant roots (Bais et al 2004;Harrison 2005;Bais et al 2006;Paszkowski 2006). For example, experiments conducted using both field soils and in vitro cultures show that compounds (e.g.…”
Section: Mechanism 3: Biochar Alters the Signaling Dynamics Between Pmentioning
confidence: 99%
“…AM obtain carbon provided by the host plant while it transfers mineral nutrients from the soil to the cortical cells. 63 Symbiosis development involves the differentiation of both symbionts to create novel symbiotic interfaces within the root cells. Phytohormone-mediated signaling through hormones, such as auxin, gibberellin, and abscisic acid, is potentially involved in the establishment of AM symbiosis.…”
Section: Fungal-produced Iaa Signaling In Plant Defense Responsesmentioning
confidence: 99%
“…For example, there are a number of reports showing that plants colonised by AM fungi are protected against subsequent infection with nematodes and plant pathogenic fungi (Borowicz 2001;Johansson et al 2004). This protection has been suggested to be due to improved nutritional status of the host but there is ample evidence that this cannot be the (only) explanation (Johansson et al 2004;Harrison 2005). Several studies have shown that during mycorrhizal symbiosis defence-related genes are induced (Pozo et al 2002;Kuster et al 2004).…”
Section: Parasitic Plant Seed Germination and Evects Of Mycorrhizationmentioning
confidence: 99%